The focus in high education: The Congress of Public Instruction (Rio de Janeiro, 1883-1884) (Foro de Educacion, 2014)
Brazilian University and Higher Education had been the subject of systematic study and research. But only recently the history of education has been addressing the education and training as a goal to be investigated. This study analyzes selected theses related to university and higher education regarding to Congress Instruction, occurred in 1883. This study allow us to highlight the most relevant ideas and proposals, adopted by an intellectual elite, which was representative of the Brazilian higher education values in the nineteenth century. The ideas of decentralization of education, gratuity, education as a mandatory issue, establishment of a national educational system, teaching formation schools, teacher training, education financial, freedom of education, co-education, popular education, public education, secularization - aimed to inspire and guide the necessary reforms, and help us to illustrated exactly why the elite show modernity educational, pedagogical innovations and achievements in more developed countries. We think it could be helpful to legitimate Brazilian proposals to improve the education system.